2020
DOI: 10.1080/17482631.2020.1799588
|View full text |Cite
|
Sign up to set email alerts
|

The intertwining of reconciliation and displacement: a lifeworld hermeneutic study of older adults’ perceptions of the finality of life

Abstract: Dalheim-Englund (2020) The intertwining of reconciliation and displacement: a lifeworld hermeneutic study of older adults' perceptions of the finality of life,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…This study is part of a larger project using a mixed-methods design to address lifestyles’ influence on community-dwelling older adults’ health (Dalheim-Englund et al, 2020 ; Gillsjö et al, 2021 ; Palmér et al, 2020 , 2020 ). The project as a whole comprises quantitative data collected through a lifestyle questionnaire and a genetic analysis of saliva samples, as well as qualitative, semi-structured interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a larger project using a mixed-methods design to address lifestyles’ influence on community-dwelling older adults’ health (Dalheim-Englund et al, 2020 ; Gillsjö et al, 2021 ; Palmér et al, 2020 , 2020 ). The project as a whole comprises quantitative data collected through a lifestyle questionnaire and a genetic analysis of saliva samples, as well as qualitative, semi-structured interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research (Dalheim-Englund et al, 2020 ; Palmér et al, 2020 , 2020 ) focusing on healthy older adults’ lives after retirement and the meaning of ageing have shown that post-retirement freedom is highly valued. Moreover, this period exposes older adults to an increased risk of illness and disease.…”
Section: Introductionmentioning
confidence: 99%
“…Choosing any interpretative support is a creative process in itself, with the advantage that it prevents one from making pre-understanding a dominating interpretative guide. Theoretical or philosophical support is perhaps most useful when it is difficult to understand meanings in data that appear to be hidden or implied, i.e., not directly pronounced and therefore not easy to discover with a completely open approach [11,32].…”
Section: Interpretative Support In a Lifeworld Hermeneutical Studymentioning
confidence: 99%
“…The lifeworld perspective reveals an opportunity to develop care that focuses on older people’s perspectives and lived experiences to strengthen health and well-being (Dahlberg et al, 2008 ). To further strengthen health and well-being among older people, the lifeworld-led caring science approach includes readiness for a caring dialogue that focuses on not only physical or social issues but also existential issues about what it means to be human and to be cared for (Palmér et al, 2020 ). Well-being should be understood as a person’s experiences of feeling well and being able to do things in life that matter to them.…”
Section: Introductionmentioning
confidence: 99%